2012
DOI: 10.1259/bjr/29806327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antenatal iodinated contrast agent on neonatal thyroid function

Abstract: Objective: The aim of this study was to assess the effect on neonatal thyroid function of iodinated contrast media administered for CT pulmonary angiography (CTPA) in babies whose mothers were investigated for suspected pulmonary embolism during pregnancy. Methods: Retrospective review of 115 pregnant patients investigated for suspected pulmonary embolism. The patient cohort consisted of two groups: Group A consisted of 73 pregnant females who received iodinated contrast agent for CTPA, and Group B (control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 31 publications
0
18
0
2
Order By: Relevance
“…Iodinated contrast crosses the placenta into the fetal circulation and is excreted through the kidneys into the amniotic fluid. 44,51,52 Studies of LOCM have demonstrated negligible risk of inducing neonatal hypothyroidism, 44,[53][54][55] and animal testing of LOCM has revealed no evidence of mutagenic or teratogenic effects, but no well-controlled studies in pregnant women have been performed. 44 For ethical reasons, such studies are unlikely.…”
Section: Administration Of Iodinated Contrast To Pregnant Womenmentioning
confidence: 99%
“…Iodinated contrast crosses the placenta into the fetal circulation and is excreted through the kidneys into the amniotic fluid. 44,51,52 Studies of LOCM have demonstrated negligible risk of inducing neonatal hypothyroidism, 44,[53][54][55] and animal testing of LOCM has revealed no evidence of mutagenic or teratogenic effects, but no well-controlled studies in pregnant women have been performed. 44 For ethical reasons, such studies are unlikely.…”
Section: Administration Of Iodinated Contrast To Pregnant Womenmentioning
confidence: 99%
“…No eff ect on foetal thyroid function has ever been reported, but a theoretical risk of iodine-induced neonatal hypothyroidism remains [49,89,96,97]. Although it is standard practice to screen all neonates for hypothyroidism, this test is particularly important in neonates born to women who re- Table IV.…”
Section: Iodinated Contrast Agentsmentioning
confidence: 99%
“…If this screening is performed, no extra attention is felt to be necessary for cases of intravenous administration of iodinated, water-soluble contrast agents at routine clinical doses during pregnancy. 24 28 29 In countries without routine screening for hypothyroidism, an extra test should be performed during the first week of life if an iodinated contrast agent was administered to the mother during pregnancy. A general rule for the imaging strategy in a pregnant patient is to intravenously administer the iodinated contrast agent for an examination that would also be performed with contrast agent if the patient was not pregnant.…”
Section: Imaging Modalitiesmentioning
confidence: 99%